2011
DOI: 10.5194/gmd-4-919-2011
|View full text |Cite
|
Sign up to set email alerts
|

The Met Office Unified Model Global Atmosphere 3.0/3.1 and JULES Global Land 3.0/3.1 configurations

Abstract: Abstract. We describe Global Atmosphere 3.0 (GA3.0): a configuration of the Met Office Unified Model (MetUM) developed for use across climate research and weather prediction activities. GA3.0 has been formulated by converging the development paths of the Met Office's weather and climate global atmospheric model components such that wherever possible, atmospheric processes are modelled or parametrized seamlessly across spatial resolutions and timescales. This unified development process will provide the Met Off… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
177
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(179 citation statements)
references
References 105 publications
2
177
0
Order By: Relevance
“…The AGCM used here, HadGEM3-GA3.0, is the Global Atmosphere 3.0 configuration of the HadGEM3 family of the Met Office Unified Model (Walters et al, 2011). We use an ensemble of simulations at three different horizontal resolutions: N96 with a grid spacing of 135 km at 50 • N, N216 (60 km), and N512 (25 km).…”
Section: Model Ensemblementioning
confidence: 99%
“…The AGCM used here, HadGEM3-GA3.0, is the Global Atmosphere 3.0 configuration of the HadGEM3 family of the Met Office Unified Model (Walters et al, 2011). We use an ensemble of simulations at three different horizontal resolutions: N96 with a grid spacing of 135 km at 50 • N, N216 (60 km), and N512 (25 km).…”
Section: Model Ensemblementioning
confidence: 99%
“…For a more detailed description of the formulation of both models, the reader is referred to Walters et al (2011). HadGEM3 is integrated for 27 years with horizontal grid spacing of 1.875°9 1.25°and 85 model vertical levels, using prescribed daily observed SST/ SICE from the Reynolds dataset (Reynolds et al 2003).…”
Section: Model Description and Experimental Designmentioning
confidence: 99%
“…The purpose of this paper is twofold: (1) explore the performance of HadGEM3-RA, the RCM configuration of the Hadley Centre Global Environmental Model version 3 (HadGEM3; Walters et al 2011), in simulating features of the WAM onset; (2) use the dynamical fields from the high resolution simulation together with the pseudo-observed fields from the ERA-Interim reanalysis (Dee et al 2011) to develop hypotheses on the dynamical factors driving the observed features of the monsoon. In this respect, comparisons of the RCM performance against that of HadGEM3, a parent GCM which shares common model components and formulation and which is not forced by pseudo-observed lateral boundaries serve to provide insights on the ability of the model physics formulation to support a realistic monsoon simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The control simulation uses the MetUM in a configuration known as Global Atmosphere 3.0 (GA3.0, Walters et al, 2011) which includes the PC2 cloud scheme and the cloud erosion parametrization given by Equations (1) and (2), while the experiment uses Equations (10) and (11). Both simulations were run for 10 years using a regular latitude-longitude grid with a grid-length of 1.24 • latitude × 1.88 • longitude.…”
Section: Results Of Climate Simulationsmentioning
confidence: 99%
“…In particular, there are reductions to the biases and root-mean-square errors for both the short-wave and long-wave CRFs. The new erosion formulation is now a candidate for inclusion in the next version of the Met Office Global Atmosphere, which will follow the configuration described by Walters et al (2011).…”
Section: Medium-range Weather Forecast Integrated Forecastmentioning
confidence: 99%